2015
DOI: 10.1177/2040622315608647
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment of spondyloarthritis: exploring the effectiveness of nonsteroidal anti-inflammatory drugs, traditional disease-modifying antirheumatic drugs and biological therapies

Abstract: Spondyloarthritis represents a heterogeneous group of articular inflammatory diseases that share common genetic, clinical and radiological features. The therapy target of spondyloarthritis relies mainly in improving patients' quality of life, controlling articular inflammation, preventing the structural joints damage and preserving the functional abilities, autonomy and social participation of patients. Among these, traditional disease-modifying antirheumatic drugs have been demonstrated to be effective in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 104 publications
(182 reference statements)
0
9
0
4
Order By: Relevance
“…The joint space is physically close to the growth zone of the condylar head, and evolutionarily it is a distinct synovial joint with a unique biochemical makeup. Moreover, there is precedent for the observation of relative responsiveness to therapy with other joints, e.g., the inability of traditional DMARDs to treat axial spondyloarthritis despite some effectiveness with these medications in the management of peripheral disease [ 45 ]. There may also be differences in the biology of arthritis in that joint; as an illustration, one study showed different epigenetic changes of fibroblast-like synoviocytes in the knee as compared to the hip of patients with rheumatoid arthritis [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…The joint space is physically close to the growth zone of the condylar head, and evolutionarily it is a distinct synovial joint with a unique biochemical makeup. Moreover, there is precedent for the observation of relative responsiveness to therapy with other joints, e.g., the inability of traditional DMARDs to treat axial spondyloarthritis despite some effectiveness with these medications in the management of peripheral disease [ 45 ]. There may also be differences in the biology of arthritis in that joint; as an illustration, one study showed different epigenetic changes of fibroblast-like synoviocytes in the knee as compared to the hip of patients with rheumatoid arthritis [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that NSAIDs are associated with mild or poor responses in elderly SpAs patients and corticosteroids are not strongly recommended because of the risk of serious long-term adverse effects, such as hypertension, diabetes, osteoporosis, skin atrophy, and cataracts. 186 Moreover, csDMARDs effectiveness and safety derived from randomized placebo-controlled trials (RCTs) and longitudinal observational cohorts are scarce and mainly focused on methotrexate and sulfasalazine. 187 Esposito et al 188 retrospectively evaluated the effectiveness and safety of subcutaneous etanercept and adalimumab in 89 elderly patients with PsO and PsA, aged between 65 and 82 years (mean age 69.7 years).…”
Section: Discussionmentioning
confidence: 99%
“…• Anti-TNF ajanlar romatoid artrit (RA), ankilozan spondilit (AS), psoriyatik artrit (PsA) ve juvenil idiyopatik artrit (JIA) gibi çeflitli romatizmal hastal›klar›n tedavisinde yayg›n olarak kullan›lmaktad›r. [11][12][13][14] • IL-1β inhibisyonu yapan biyolojik tedavi ajanlar› bafll›ca ailesel Akdeniz atefli (FMF) gibi otoinflamatuvar hastal›klar›n ve baz› J‹A olgular›n›n tedavisinde kullan›lmaktad›r. [5] • IL-6 inhibisyonu yapan TCZ bafll›ca RA tedavisinde ve JIA'n›n sistemik ve poliartiküler formlar›n›n tedavisinde kullan›lmaktad›r.…”
Section: Biyolojik Tedavi Ajanlar› Etkilerini Nas›l Göstermektedir?unclassified
“…Dolay›s›yla anti-TNF ajanlar bu hastal›klar›n tedavisinde baflar›yla kullan›labilmektedir. [4,[11][12][13][14] Gerçekten de, çeflitli anti-TNF ajanlar›n bu hastal›klarda etkinli¤i ve güvenlili-¤i çeflitli klinik çal›flmalarda gösterilmifltir. Bu nedenle, anti-TNF ajanlar›n romatoloji prati¤indeki baflar›s›n›n, di¤er biyolojik tedavilere öncülük etti¤i ve teflvik edici oldu¤u söylenebilir.…”
Section: Tümör Nekrotizan Faktör ‹Nhibitörleriunclassified
See 1 more Smart Citation